Integration of Cocoa and Cattle Towards Production and Creation Body Weight of Cattle - Muthia Muhsana Mukhlis; Abd Haris Bahrun (Journal of Global Innovations in Agricultural Sciences)
Cocoa is one of the main plantation crops in North Kolaka, Southeast Sulawesi, and is a strategic plantation commodity that tends to be important for the national economy because it provides employment, a source of foreign exchange, and a source of income for farmers. Manure is a waste product from livestock manure, one of which is cattle, which can be used to add nutrients and improve the physical and biological properties of soil. Integrated agriculture (crop-livestock integration) is an agricultural system characterized by the interrelationship between crop and livestock components in a farming business or an area. This study was conducted to determine the effect of manure on cocoa crop production, and to find out that feed made from cocoa fruit peel waste can increase the body weight of cattle. To find out how cattle manure and cattle feed using cocoa shell waste can be integrated in increasing cocoa production and increasing body weight in cattle. Based on the results of the research conducted, it was found that the cattle manure treatment showed the best results for each parameter observed in cocoa production, while in the cattle parameter, the provision of additional cocoa peel feed gave the highest results.